Breast cancer related lymphoedema (BCRL): Prevalence and evaluation of risk factors - Rohit Srivastava, Sunil Kumar singh*, Amarjot Singh, Priyanka Rai, Mushtaq Ali (Innovative Journal of Medical and Health Sciences, 2020)
Among cancer related mortality and morbidity, the Breast cancer is commonest cause in women worldwide . Despite of improved treatment technique of the breast cancer, the incidence some refractory complications like breast cancer related lymphoedema (BCRL) of corresponding arm has increased ,which is related to treatment modalities like axillary staging, axillary irradiation or both . BCRL is an agonizing complication which limits day to day activity of the patient and becomes more relevant as the survival after diagnosis of breast cancer increases. Due to lack of standard definition and standardized criteria for evaluation, the incidence varies. This Cohort study with historical cohort and prospective follow-up for 1 year aimed to determine the prevalence , risk factors, influence of axillary staging and locoregional radiotherapy in the development of BCRL . Methods: From May 2017 to March 2019 , clinical records of 180 Breast cancer patients were reviewed from 3 different institutes with Stage I to stage III breast cancer treated with BCT(breast conservation surgery ), MRM (Modified Radical Mastectomy ) and RT( Radiotherapy) in addition to systemic chemotherapy and the patients were followed up till 1 year. Data were recorded in terms of age, menopausal status, body mass index (BMI) and presence of co-morbid conditions. Difference between both upper limb circumferences at any level of more than 2 cm was considered as significant lymphoedema. With the help of SPSS software, all the statistical calculation was done. Results: The prevalence of clinically significant lymphedema was 32.7%. The prevalence of lymphedema was 34% % in patients treated with MRM where as it was 20% in patients treated with Breast conservative surgery. Among sub group of MRM in which more than 4 LN came to be positive were having significant lymphedema( 42%) as compared to less than 4 LN positive patients(21%). It was observed that BMI(Body mass index), presence of co-morbid conditions and chemotherapy were not significantly associated with BCRL. Post-operative radiotherapy (axillary irradiation) appears to be an independent risk factor for development of BCRL in multivariate analysis (P < 0.001) Conclusion: In our cohort of breast cancer patients, the prevalence of lymphedema was higher in BMI >25kg/m2 patients . Women who underwent MRM with more than 4 positive lymph nodes had significantly more number lymphedema patients . Radiotherapy was found to be independent risk factor for the development lymphedema, suggesting that the combination of axillary staging and radiation therapy puts patient at much higher risk of lymphedema development. Key words: Breast cancer–lymphoedema